Effects of biodegradable hydrogel spacer injection on contralateral submandibular gland sparing in radiotherapy for head and neck cancers. Issue 1 (January 2018) - Rao, Avani D.; Coquia, Stephanie; De Jong, Robert; Gourin, Christine; Page, Brandi; Latronico, Diane; Dah, Samson; Su, Lin; Clarke, Stephen; Schultz, Jeffrey; Rosati, Lauren M.; Fakhry, Carole; et al.
Abstract: Xerostomia is the most common late toxicity after head and neck radiation. We demonstrate injection of a hydrogel spacer anteriorly displacing the submandibular gland. This procedure enables reduced dose to the displaced submandibular gland in cadaveric models of oropharynx cancer treated with IMRT, with potential implications in reducing xerostomia risk.